Refractory nummular eczema in child successfully treated with NB‐UVB and topical delgocitinib - Ichiro Kurokawa; Jun‐Ichiro Ono (Frontiers Media S.A., 2022)
Refractory nummular eczema with atopic dermatitis in child successfully treated with narrowband ultraviolet B (NB‐UVB) and topical delgocitinib was reported. The combination of NB‐UVB and topical delgicitinib can be one of alternative treatments for refractory nummular eczema in children.